Revitalizing the Tangerang Old Market Area (Case Study: Kota Lama Tangerang) - Martini, Elsa; ardiansyah, Andri; Martina Kasikoen, Ken; Latif Jaohari, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
One of the historical centers of Tangerang City which still shows remnants of the past is the Old Market area. It is located not far from the Cisadane River. Tangerang Old Market is the oldest traditional market ever and is the forerunner of the City of Tangerang. Almost no longer visible historical buildings in the city of Tangerang began to be destroyed in the place of skyscrapers, so that there is no longer any cultural or historical value attached to the city of Tangerang. But there are still some museums or historical buildings that still exist, only the lack of cultural preservation and historical information to the community, so that people do not know even forget the importance of historical values. Based on the conclusions from the analysis of the old market area of Tangerang, the image of the quality of historic buildings has decreased, promotional activities through print and online media are less than optimal and there is no government socialization to the community so that the public is lacking knowledge about the importance of preserving cultural heritage.